The Palgrave Literary Dictionary of Samuel Taylor Coleridge - Garrett, Martin. author. aut Link
XVIII, 210 p.
Keywords: This volume explores ‘the labyrinth of what we call Coleridge’ (Virginia Woolf): his poems and prose, their sources, interpretation and reception; his life, troubled marriage and fatherhood, conversation, changing intellectual contexts and legacy. Major entries cover such canonical works as The Rime of the Ancient Mariner, Christabel, ‘Kubla Khan’, the ‘conversation poems’ and Biographia Literaria. But a fuller understanding of Coleridge must embrace many lesser-known poems – lyrics, satire, comical squibs. The prose – critical, philosophical, political, religious – ranges from his early radical writings to the more conservative On the Constitution of the Church and State, his influential Shakespeare lectures, and the vast resource of the notebooks. Coleridge read widely throughout his life and engaged extensively with the work of, among many others, Milton, Fielding, Berkeley, Priestley, Kant, Schelling. One of his most important relationships was with William Wordsworth. Another was with Sara Hutchinson. Entries trace Coleridge’s changing reputation, from brilliant young activist to the ‘Sage of Highgate’ to the later apostle of the theories of the imagination and of Practical Criticism. Other topics covered include opium, plagiarism, the French Revolution, Pantisocracy, Unitarianism, and the Salutation and Cat tavern.